(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe certain characteristics of Type 2 Diabetes Mellitus (T2DM) patients with complications and analyze the direct medical treatment costs for these patients at Chiêm Hóa General Hospital in 2023. Methods: This is a cross-sectional descriptive study using electronic medical records of 1953 T2DM patients with complications receiving outpatient treatment at the Endocrinology Department of Chiêm Hóa General Hospital in 2023. Results: Among the study subjects, 52.64% were male and 47.36% were female, predominantly aged 60-70 years and above 70 years. Neurological complications (36.04%) and cardiovascular complications (31.54%) were the most common. Among the cost components, the average annual medication cost was the highest at 4,592,936 VND per year. The total expenditure for renal complications was the highest (9,175,619 ± 4,256,098 VND). Conclusion: The study provides a comprehensive overview of the disease status and medical costs for the treatment of T2DM with complications in Vietnam, highlighting the significant dependence on medication and testing costs. It underscores the importance of blood glucose control, regular disease management, and minimizing risk factors to prevent severe complications.